Conservation Genetics and the Management of Endangered Fishes - Meffe, Gary K. (Fisheries, 2011)
The emerging field of endangered fishes management has yet to fully incorporate conservation genetics into recovery programs. Genetic aspects of small populations must be considered at the outset of management programs in order to maximize probability of their long‐term survival and continued adaptability. Total genetic variance of a species consists of within population genetic diversity, and the differences found among populations; both types of variance should be maintained to maximize adaptive flexibility of endangered fishes. Forces that erode genetic variation include small population size, population bottlenecks, genetic drift, inbreeding depression, artificial selection in captivity, and mixing of distinct genetic stocks. These can lead to increased homozygosity, loss of quantitative variation, and exposure of deleterious recessive alleles, all of which may reduce fitness. Suggestions for genetically sound management of endangered fishes include genetic monitoring of natural and captive populations, use of large numbers for captive breeding where feasible, selective mating to avoid inbreeding where necessary, minimization of time in captivity, and separate maintenance of distinct stocks.